EPR of gamma-induced paramagnetic centers in tellurite glasses - Giehl, J. M. [UNESP]; Pontuschka, W. M. [UNESP]; Barbosa, L. C.; Ludwig, Z. M. C. (Elsevier B.V., 2010)
Intrinsic paramagnetic responses were observed in the 60TeO(2)-25ZnO-15Na(2)O and 85TeO(2)-15Na(2)O mol% glasses, after gamma-irradiation at room temperature: (1) a shoulder at g(1) = g(parallel to) = 2.02 +/- 0.01 and an estimated g(perpendicular to)similar to 2.0 attributed to tellurium-oxygen hole center (TeOHC); (2) a narrow resonance at g(2)= 1.9960 +/- 0.0005 related to the modifiers and (3) a resolved resonance at g(3) = 1.9700 +/- 0.0005 ascribed to a tellurium electron center (TeEC) of an electron trapped at an oxygen vacancy (V(o)(+)) in a tellurium oxide structural center. It is suggested that the creation of (NBO(-),V(o)(+)) pair follows a mechanism where the modifier oxide molecule actuates as a catalyser. An additional model for the NBO radiolysis produced by the gamma-irradiation is proposed on the basis of the evolution of the g(1), g(2) and g(3) intensities with increasing dose (kGy). Crown Copyright (C) 2010 Published by Elsevier B.V. All rights reserved.
Keywords: Tellurite glasses; Electron paramagnetic resonance (EPR); Defect centers